New splicing pathogenic variant in EBP causing extreme familial variability of Conradi–Hünermann–Happle Syndrome. (December 2018) - Pacault, Mathilde; Vincent, Marie; Besnard, Thomas; Kannengiesser, Caroline; Bénéteau, Claire; Barbarot, Sébastien; Latypova, Xénia; Belabbas, Khaldia; Lamazière, Antonin; Winer, Norbert; Joubert, Madeleine; Bézieau, Stéphane; et al.
Abstract X-linked dominant chondrodysplasia punctata (CDPX2 or Conradi-Hünermann-Happle syndrome, MIM #302960) is caused by mutations in theEBP gene. Affected female patients present with Blaschkolinear ichthyosis, coarse hair or alopecia, short stature, and normal psychomotor development. The disease is usually lethal in boys. Nevertheless, few male patients have been reported; they carry a somatic mosaicism inEBP or present with Klinefelter syndrome. Here, we report CDPX2 patients belonging to a three-generation family, carrying the splice variant c.301 + 5 G > C in intron 2 ofEBP . The grandfather carries the variant as mosaic state and presents with short stature and mild ichthyosis. The mother also presents with short stature and mild ichthyosis and the female fetus with severe limb and vertebrae abnormalities and no skin lesions, with random X inactivation in both. This further characterizes the phenotypical spectrum of CDPX2, as well as intrafamilial variability, and raises the question of differential EBP mRNA splicing between the different target tissues.